Framing options for characterising and parameterising human agents in empirical ABM. (July 2017) - Smajgl, Alex; Barreteau, Olivier
Abstract: This paper provides empirical agent-based modellers with a generic framework that allows for a structured and unambiguous description of the characterisation and parameterisation process. As methodological recommendations depend on contextual circumstances cases are defined to distinguish particular modelling situations, which require different methods for robust model characterisation and parameterisation. Both combined allows in a comparative perspective for analysing how effectively different (sequences of) methods perform in similar contexts. Highlights: We synthesise a range of experiences to guide the parameterisation of empirical ABM. This paper provides a revised framework, tested on eleven empirical ABM. We define empirically-derived categories of modelling situations. We synthesise key lessons learnt on the parameterisation of empirical ABM. We present replicable parameterisation techniques for empirical ABM.